The Pengaruh Pemasaran Konten melalui Instagram @Rockbarbali terhadap Minat Beli Tamu di Rock Bar Bali - Noviari Wedanti, Dewa Ayu; Diwyarthi, Ni Desak Made Santi; Adinda, Clearesta (Program Studi Administrasi Perhotelan, 2025)
This study aims to investigate the influence of firm generated content and electronic word of mouth on the purchase intention of guests at Rock Bar Bali. Data was collected through questionnaires distributed to followers of Rock Bar's Instagram account and analyzed using SPSS version 25. The data analysis techniques used in this study were classical assumption tests, multiple linear regression analysis, t-tests, F-tests, coefficient of determination, and effective contribution. The results of the study show that firm generated content and electronic word of mouth have a significant and positive effect on the purchase intention of guests. The contribution of these two variables to purchase intention reached 73.5%. These findings suggest that marketing strategies that focus on creating quality content and encouraging positive reviews from visitors can be an effective strategy to increase purchase intention at Rock Bar Bali.